TCR-CD3 signal strength regulates plastic coexpression of IL-4 and IFN-γ in Tfh-like cells - Verstegen, Niels J. M.; Jorritsma, Tineke; ten Brinke, Anja; Barberis, Matteo; van Ham, S. Marieke (Frontiers in Immunology, 2024)
The development of T follicular helper (Tfh) cells is an ongoing process resulting in the formation of various Tfh subsets. Despite advancements, the precise impact of T cell receptor (TCR) stimulation on this process remains incompletely understood. This study explores how TCR-CD3 signaling strength influences naive CD4 + T cell differentiation into Tfh-like cells and the concurrent expression of interleukin-21 (IL-21), interleukin-4 (IL-4), and interferon-gamma (IFN-γ). Strong TCR-CD3 stimulation induces proliferation and increased IL-21 expression in Tfh-like cells, which exhibit a characteristic phenotype expressing CXCR5 and PD1. The coexpression of IL-4 and IFN-γ in IL-21producing Tfh-like cells is controlled by the strength TCR-CD3 stimulation; low stimulation favors IL-4, while strong stimulation enhances IFN-γ secretion. Exogenous addition of the effector cytokines IL-21 and IL-4 further modulate cytokine coexpression. These findings highlight the intricate regulatory mechanisms governing cytokine production and plasticity in Tfh-like cells, providing insights into B cell response modulation. In vivo, antigen availability may regulate Tfh cell plasticity, impacting subsequent B cell differentiation, emphasizing the need for further exploration through animal models or antigen-specific Tfh cell analyses in human lymph node biopsies.